2015
DOI: 10.1186/s13027-015-0008-y
|View full text |Cite
|
Sign up to set email alerts
|

Global availability of data on HPV genotype-distribution in cervical, vulvar and vaginal disease and genotype-specific prevalence and incidence of HPV infection in females

Abstract: BackgroundCountry-level HPV genotyping data may be sought by decision-makers to gauge the genotype-specific burden of HPV-related diseases in their jurisdiction and assess the potential impact of HPV vaccines. We investigated, by country, the availability of published literature on HPV genotypes in cervical, vaginal and vulvar cancers and intraepithelial neoplasms (CINs, VaINs and VINs) and on prevalence and incidence of genital HPV infections among women without clinically manifest disease.FindingsPrimary sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 11 publications
2
24
1
2
Order By: Relevance
“…The presence of HPV in normal samples is also shown in other studies [2,22,23]. In a study performed in the city of Porto Alegre, the prevalence of HPV was demonstrated in 11.6% of women without LSIL or HSIL [25].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The presence of HPV in normal samples is also shown in other studies [2,22,23]. In a study performed in the city of Porto Alegre, the prevalence of HPV was demonstrated in 11.6% of women without LSIL or HSIL [25].…”
Section: Discussionsupporting
confidence: 69%
“…Among the most common HPV types, genotypes 16, 18, 31, 33, 45, 52 and 58 are responsible for approximately 90% of cervical cancers [22]. In Brazil, Oliveira et.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of variants such as monovalent (HPV16), bivalent (HPV16 and 18), quadrivalent (HPV6, 11, 16 and 18) and nonavalent (HPV6,11,16,18, 31, 33, 45, 52 and 58) vaccines (5,6). In Vietnam, the measures for cervical cancer prevention include, primary screening for HPV and vaccination against HPV (7).…”
Section: Abstract Aim: the Goal Of The Present Study Was To Determinmentioning
confidence: 99%
“…Доказано, что самой распространенной патологией, ведущей к развитию пред-раковых заболеваний, является папилломавирусная ин-фекция (ПВИ), передающаяся половым путем [1][2][3][4][5][6][7][8].Невиданное доселе обновление технологического обеспечения, произошедшее на рубеже XX-XXI веков, совершенствование методов диагностики вирусных забо-леваний способствовали не только выявлению истинной частоты инфицированности вирусом папилломы челове-ка (ВПЧ), но и изучению связи между инфицированно-стью ВПЧ и диспластическими процессами шейки матки [8][9][10][11][12]. Доказано, что репликация ВПЧ на начальном эта-пе приводит к возникновению воспалительной реакции в шейке матки, а в последующем -к возникновению в тол-ще эпителиального слоя атипичных клеток с различной степенью нарушения их дифференцировки, к изменени-ям слоистости эпителиальных клеток (без участия в пато-логическом процессе стромальных структур).…”
unclassified
“…(ПИП) [8][9][10][11][12]. Плоскоклеточное интраэпителиальное поражение шейки матки классифицируется как ПИП низкой (LSIL -low-grade squamous intraepithelial lesions) и высокой (HSIL-high-grade squamous intraepithelial lesions) степени выраженности в зависимости от уровня патоло-гического роста клеток.…”
unclassified